A Genetic Algorithm Based Multi-modal Biometric Recognition System Using Iris and Fingerprint (International Journal of Food and Nutritional Sciences, 2021)
In today’s sensitive era, an accurate personal authentication has become a major challenge in wide category ofapplication domains. Currently, most of the biometric systems employed are based on single biometric traitwhich is named as uni-biometric systems